2006
DOI: 10.1164/rccm.200511-1808oc
|View full text |Cite
|
Sign up to set email alerts
|

Multicenter Randomized Controlled Trial of Withdrawal of Inhaled Corticosteroids in Cystic Fibrosis

Abstract: Rationale: Lung inflammation and injury is critical in cystic fibrosis. An ideal antiinflammatory agent has not been identified but inhaled corticosteroids are widely used despite lack of evidence. Objectives: To test the safety of withdrawal of inhaled corticosteroids with the hypothesis this would not be associated with an earlier onset of acute chest exacerbations. Methods: Multicenter randomized double-blind placebo-controlled trial in 18 pediatric and adult UK centers. Eligibility criteria included age Ͼ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(73 citation statements)
references
References 37 publications
1
68
0
4
Order By: Relevance
“…Antiinflammatory strategies such as alternate-day prednisolone have been shown to be effective in CF [99], but need to be formally trialled in PCD before they could be recommended. There are no data on which to recommend or avoid inhaled corticosteroids; by analogy with CF [100], they are probably best avoided unless they can be shown to be of definite benefit in an individual patient.…”
Section: Anti-inflammatory Strategiesmentioning
confidence: 99%
“…Antiinflammatory strategies such as alternate-day prednisolone have been shown to be effective in CF [99], but need to be formally trialled in PCD before they could be recommended. There are no data on which to recommend or avoid inhaled corticosteroids; by analogy with CF [100], they are probably best avoided unless they can be shown to be of definite benefit in an individual patient.…”
Section: Anti-inflammatory Strategiesmentioning
confidence: 99%
“…Although this represents a very high prevalence, asthma is much more common in children with CF, where the rate of bronchial hyper-responsiveness approaches 50%, and up to 10-15% may experience a hyper-IgE asthma variant known as allergic bronchopulmonary aspergillosis (ABPA). [29][30][31][32][33][34][35][36][37][38][39][40] ABPA is characterized by a predominantly Th2-mediated immune response to inhaled Aspergillus antigens in the airways, leading to reversible airway obstruction and bronchial hyper-reactivity. This inflammatory response correlates with the local infiltration of effector cells including mast cells, activated neutrophils, eosinophils, basophils and macrophages into the airway mucosa and the airway lumen.…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have demonstrated the ineffectiveness or the occurrence of adverse side-effects of approaches involving inhaled steroids [8] and a leukotriene (LT)B 4 antagonist [9]. A major difficulty in evaluating anti-inflammatory treatments in clinical trials remains selection of appropriate outcome measures (table 1).…”
mentioning
confidence: 99%